Letter - Pontefract Central Strike Committee, 6 May 1926 (page 2)
1926-05-06 "Letter - Pontefract Central Strike Committee, 6 May 1926 (page 2)" [g0103002.jpg], 6 May 1926, Pontefract Central Strike Committee